Linking Representative Household Models with Household Surveys for Poverty Analysis: A Comparison of Alternative Methodologies - Agénor, Pierre-Richard; Chen, Derek H.C.; Grimm, Michael (World Bank, Washington, D.C., 2013)
The authors compare three approaches to linking representative-household macro models with micro household income data in terms of their implications for measuring the poverty and distributional effects of policy shocks. These approaches are a simple micro-accounting method, an extension of that method to account for changes in employment structure, and the Beta distribution approach. Even though in the authors simulation exercises the three methods do not lead to fundamentally different results in absolute terms, they show that potential differences in the measurement of distributional and poverty effects of policy shocks can be very large.